Investigation of the mutagenic effects of aluminium trioxide implants on embrions in experimental animals - Zelić Obrad; Arsenijević Vladimir; Đukanović Dragoslav; Dimitrijević Božidar; Markov Jasmina; Lekić-Charles Predrag (Serbian Medical Society - Dental Section, Belgrade, 2002)
Several diseases as well as trauma can affect the composition and integrity of periodontal tissues loading eventually to the destruction of connective tissue matrix and cells, loss of attachment and resorption of alveolar bone often followed by tooth loss. Replacement of the missing tooth could then be provided by endosseous dental implants healing in a form of osseo -or fibrosseal integration to the alveolar bone. Aluminium oxide ceramics, a form, of endosseous implant, allows osseointegration type of healing and has demonstrated excellent biocompatibility. However, potential aluminium toxicity has been implicated in the pathogenesis of a number of clinical disorders and for this reason we examined the reproductive and mutagenic effect of aluminium trioxide ceramic implant in experimental mice. 720 female and 45 fertile male BALB-cAn NCR mice were included in the study. 3 experimental groups of fertile male mice (15 for each group) were treated with an intraperitoneal injection of aluminium trioxide (I g/kg of body weight, group I), with ethyl-methane-sulphonate as a positive control (200 mg/kg, group II) and with Tween-80 (10 ing/kg as negative control, Group III). Each of the labeled male mice fertilized previously uncoupled female mice during 8 weeks (a pair per week) to facilitate appropriate pre-and post-meiotic conditions of spermatogenesis to occur. Female mice were sacrificed with cervical dislocation at day 13 after fertilization. Immediately upon sacrifice the uterus was removed and the number of alive and healthy, or alive but mutated and/or dead embryos was computed to determine the dominant lethal of mutagenic effects. Animals treated with aluminium trioxide demonstrated similar effects on the reproductive and mutagenic capacity as the negative control, whereas the animals treated as positive controls exhibited significantly reduced reproductive and mutagenic capacity. Collectively, we concluded that aluminium trioxide has a very low rate of embryonal mortality and mutagenicity in mice. This finding is in general agreement with the biocompatibility of aluminium trioxide (Aldovit) as an implant material.